A Note on J. v. Neumann's Article on "A Model of Economic Equilibrium" - Champernowne, D. G. (Review of Economic Studies, 1945)
Journal Article A Note on J. v. Neumann's Article on "A Model of Economic Equilibrium" Get access D. G. Champernowne D. G. Champernowne Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 13, Issue 1, 1945, Pages 10–18, https://doi.org/10.2307/2296112 Published: 01 April 1945